Development Of Salmonella Typhi Ty21a As A Potential Oral Vaccine Against Tuberculosis : Surface Display And DNA Vaccine Carrier Of A Synthetic Multi-Epitope Mycobacterial Gene [RC311.4. A135 2004 f rb][Microfiche 7750]. - Ahmad Sarhan, Mohammed Abdel Aziz (2004)
Despite the discovery of the causative agent of tuberculosis (TB), Mycobacterium tuberculosis, more than 120 years ago TB remains a major worldwide health problem.